Developing Interactive E-Learning Website For Learners Engagement In Photography - Alatsheh, Hamad Mousa (2011)
The purpose of this project is to discuss how to develop an effective e-learning web site which support learners\' interactivity, engagement and enjoyment. To fulfill the purpose of this research, the researcher developed an interactive e-learning web site to support learners\' engagement and enjoyment in learning photography.